A systematic review on the influence of product placement (PPL) in Korean drama and its effects towards youth purchase intention on Korean products in Malaysia / Wan Nurdayana Che Wan Mohd Khair - Che Wan Mohd Khair, Wan Nurdayana (Faculty of Communication and Media Studies (FCMS), 2022)
This systematic review synthesised evidence on the influence of K-drama content on purchase intentions among Malaysian youth. The Korean wave has been infiltrating the Malaysian landscape since 2010, and K-dramas, has gained in popularity, particularly from the younger generation. Watching Korean culture and products that the actors portrayed had influenced the youth to purchase Korean products, especially from the brands advertised as Product Placement (PPL). This study employs Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), based on papers in the Google Scholar database. A search of the Google Scholar database reaped four eligible studies. This paper includes research papers from 2018 to April 2022, including keywords 'product placement in K-drama' and 'purchase intention' and 'Malaysia' and 'youth'. Findings included factors that affect youth's purchase intention towards Korean products featured in K-dramas as PPL: social value, social attachment, idolisation towards their favourite celebrities and positive perception towards K-drama content and the Korean culture. Due to methodological constraints in cross-sectional design, sampling, and measures, there are significant constraints in the findings. The interest shown by young adults towards Korean content and consumption of Korean products is often discussed. The topic should be measured more through qualitative enquiries, explored further in various age groups and variables related to the effect of PPL displayed in entertainment products.